Design and analysis of cable-driven mechanical gripper for complex manipulation. (July 2020) - Zhang, Deyang; Cheng, Bo; Yue, Zhiyong
Abstract: This paper studies the design and analysis problem of a class of cable-driven mechanical gripper for complex object manipulations. More precisely, a new structure design of mechanical gripper with cable-driven mechanism is first proposed with details for effective object grasping. In addition, an effective method is developed to prevent overload of axial rotation torque of the gripper. Based on the designed gripper, the kinematic analysis is then carried out and the caging grasp analysis is shown.